Examining the organization and quality of the psychiatric consultative service in Norway. (2nd January 2019) - Weisser, Kristin Howlid; Diseth, Trond H.; Boye, Birgitte; Faerden, Ann; Ekeberg, Øivind
Abstract: Aim: Patients admitted to somatic departments may face psychiatric challenges, such as suicidal behavior, substance abuse, crisis reactions, or somatoform disorders. Mental disorders can complicate the diagnosis and treatment of a somatic disorder. The Consultation-Liaison Psychiatry Service (CLP) can provide advice and guidance to attending staff in somatic departments. CLP in Norwegian hospitals was last reviewed in 1997. There is insufficient awareness of the service as it currently stands. This specialist field is expanding, and there is a need to examine how the service is organized at present and how it works. Materials and methods: A study of the scope, quality, availability, content, and organization of the psychiatric consultative service was conducted in February–March 2016. The study also examined whether service users and providers were satisfied with the service, the content of the service, and whether they considered the service to be adequate. Results and conclusions: Although CLP has expanded over the last three years, somatic and psychiatric departments wish for its further expansion. The service provision is at an acceptable level during the daytime, but not during weekends and holidays. We found that 20% of all referrals are rejected and that 80–90% of all physicians wanted outpatient services for short-term follow-up and for help with undiagnosed, unclear, unexplained, (indeterminate) conditions. Discussion: The service works satisfactorily during ordinary working hours. There is a need to establish outpatient services and to strengthen the services outside these hours. Collaborative research should be further developed.